THE NATUR OF SOVIET-TURKISH RELETIONS DURING THE FORMATION OF THE REPUPLIC OF TURKEY - O. E. Guliyev (Современная наука и инновации, 2023)
This article examines the period of formation of Soviet-Turkish relations in the context of geopolitical challenges. Modern Russian-Turkish relations play a key role in resolving conflicts in the Middle East. For the further development of regional cooperation, it is necessary to separately consider and conduct a historical analysis of Soviet-Turkish relations during their formation. In this research paper, the formation of Soviet-Turkish relations is considered comprehensively, bilateral and multilateral agreements are used. The methodological basis of this scientific work was the historical-comparative approach, which made it possible to compare bilateral relations in historical retrospect, as well as to compare Soviet and Western diplomatic approaches in bilateral relations during the period under study. Also, such methods of analyzing the topic as the study of documentary sources and historiography in Russian and Turkish, and their comparison and comparison were applied. Analyzing the formation and nature of Soviet-Turkish relations, one can distinguish: political, military, ideological and economic reasons for rapprochement. Historically, bilateral relations have been hostile, antagonisms existing between the two geopolitical actors have led to military clashes. Drastic changes took place, after the First World War, two once powerful empires ceased to exist. For the Turkish people, as well as the Russian, there was a question of preserving independence and territorial integrity. Similar historical processes have played the role of a unifying factor for the two states. The basis of allied relations between Soviet Russia and Turkey was laid by V.I. Lenin and M. K. Ataturk. Surrounded by interventionists, the national liberation movement of Turkey was in search of an external ally. The only political force ready to unconditionally support the liberation movement was Soviet Russia. The final victory of the national liberation movement in Turkey and the formation of the USSR served as the basis for the transition from the multi-party relations of the Soviet republics with Ankara to bilateral diplomatic ties.